ENTREPRENEURSHIP SELF-EFFICACY, ATTITUDES TOWARDS ENTREPRENEURSHIP, AND STUDENT'S ENTREPRENEURSHIP INTEREST - Dismas Persada Dewangga Pramudita (Universitas Airlangga, 2021)
One of the causes of large number unemployement is an imbalance between number of jobs and number of job applicants. Total population of Indonesia in September 2020 has reached 270 million (BPS, 2021). The Central Statistics noted that there are quite a large number of unemployed college graduates (BPS, 2020). Increasing number of entrepreneurs is considered to be one of solutions to reduce unemployment. This study aims to determine an effect of entrepreneurial self-efficacy on entrepreneurial intention directly or through attitudes towards entrepreneurship. This research was conducted at a private university in Yogyakarta with Informatics Engineering student respondents. Research data processing was carried out by Partial Least Square 3 software. The results of this study indicate that entrepreneurial self-efficacy has a direct and positive effect on entrepreneurial intention. Then, attitudes towards entrepreneurship have been shown to play a role as a mediator in relationship between entrepreneurial self-efficacy and entrepreneurial intention. Based on these results, mediating role of attitudes towards entrepreneurship is partial mediation. The results of this study are expected to be useful to encourage higher education institutions and government to motivate younger generation, especially Informatics Engineering students, to have an entrepreneurial spirit and have a positive attitude towards entrepreneurial behavior so that they are interested in becoming entrepreneurs. Informatics Engineering students are expected to be able to support economic recovery due to Covid-19 pandemic through works in form of software.